Combined surgery for large macular hole in complicated cataract: case report (retracted article) - M.M. Bikbov; O.I. Orenburkina; A.A. Zinnatullin; A.L. Yarmukhametova; A.E. Babushkin; M.R. Kalanov (РМЖ "Клиническая офтальмология")
M.M. Bikbov, O.I. Orenburkina, A.A. Zinnatullin, A.L. Yarmukhametova, A.E. Babushkin, M.R. Kalanov Ufa Research Institute of Eye Diseases of the Bashkir State Medical University, Ufa, Russian Federation The only effective treatment for macular holes (MH) is surgery. Published data demonstrate that surgery (vitrectomy, internal limiting membrane/ILM peeling, and vitreous tamponade) of small and medium MHs is usually highly effective. Meanwhile, good outcomes and a high recurrence rate of large MHs postoperatively remain challenges. The authors propose a surgical technique for MHs in complicated cataracts (patent of the RF No. 2731794 dated 09/08/2020) that involves vitrectomy, posterior hyaloid removal, ILM staining, ILM peeling, formation of a flap from the anterior lens capsule to close MH, and air tamponade. This paper describes a woman who underwent combined surgery for cataract and MH as described. The technique provided a complete and stable anatomical outcome. After 1 month (i.e., after complete resorption of air), the best-corrected visual acuity of the right eye increased to 20/40. IOP was 19.0 mm Hg. Keywords: vision, idiopathic macular hole, retina, anterior les capsule, surgery, postoperative follow-up. For citation: Bikbov M.M., Orenburkina O.I., Zinnatullin A.A., Yarmukhametova A.L., Babushkin A.E., Kalanov M.R. Combined surgery for large macular hole in complicated cataract: case report. Russian Journal of Clinical Ophthalmology. 2023;23(3):152–156 (in Russ.). DOI: 10.32364/2311-7729-2023-23-3-7.